EVALUATION OF OPERATION LOAD FOR IMPRESSION-FREE PREFORMING BY BUCKLING AT FORGINGS MANUFACTURING - Kukhar, V. V.; Prysiazhnyi, A. H.; Serdiuk, O. I. (Problems of Tribology, 2018)
This paper presents the results of experimental studies of load characteristic changes during the upsetting of high billets with the upsetting ratio (height to diameter ratio) from 3.0 to 6.0, which is followed by buckling. Such pass is an effective way of pre-forming the workpiece for production of forgings with a bended axis or dual forming, and belongs to impression-free (dieless) operation of bulk forming. Based on the experimental data analysis, an engineering method for calculation of workpiece pre-forming load as a maximum buckling force has been developed. The analysis of the obtained data confirmed the possibility of performing of this pre-forming operation on the main forging equipment, since the load of shaping by buckling does not exceed the load of the die-forging.